1998
DOI: 10.1023/a:1005993408270
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have isolated two maize cDNAs and the corresponding genes encoding fatty acid desaturase with Arabidopsis thaliana FAD7 gene as a probe. They shared almost 90% identity at DNA sequence level. Northern analysis revealed that both genes are expressed in leaves, but not in roots at normal temperature- and low temperature-growth condition. The overall level of these transcripts are elevated upon exposure to low temperature. The tissue-specific expression and DNA sequence data indicate that both genes encode pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(46 citation statements)
references
References 27 publications
4
41
0
Order By: Relevance
“…Three replicates were averaged and the standard deviation is shown in cotton (Kargiotidou et al 2008), PoleFAD2 in purslane (Teixeira et al 2009) and PlFAD2 in Phaseolus lunatus (Zhang et al 2011) were induced by cold stress. FAD8 was also induced by low temperatures in A. thaliana (Gibson et al 1994), maize (Berberich et al 1998), rice (Wang et al 2006), Descurainia sophia (Tang et al 2007) and purslane (Teixeira et al 2010). Our results showed that there was a greater expression of two FAD genes during 6°C treatment in fingered citron leaves (Fig.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Three replicates were averaged and the standard deviation is shown in cotton (Kargiotidou et al 2008), PoleFAD2 in purslane (Teixeira et al 2009) and PlFAD2 in Phaseolus lunatus (Zhang et al 2011) were induced by cold stress. FAD8 was also induced by low temperatures in A. thaliana (Gibson et al 1994), maize (Berberich et al 1998), rice (Wang et al 2006), Descurainia sophia (Tang et al 2007) and purslane (Teixeira et al 2010). Our results showed that there was a greater expression of two FAD genes during 6°C treatment in fingered citron leaves (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…The genomic sequence of CmsFAD8 was 2,751 bp and contained eight exons and seven introns (Fig. 3), similar to FAD8 genes from other higher plants (Gibson et al 1994;Berberich et al 1998).…”
Section: Isolation and Characterization Of Cmsfad2 And Cmsfad8 From Fmentioning
confidence: 63%
“…Chilling stress inhibits photosynthesis by the process of photoinhibition (Xu et al, 1999;Zhang et al, 2011). Previous research suggested that plant tolerance to chilling is dependent on unsaturated fatty acid levels (Berberich et al, 1998;Mikami & Murata, 2003). In the present study, we investigated the effects of chilling stress on the photosynthesis, antioxidant enzyme and unsaturated fatty acids in membrane lipids on seedlings growth of two sweet sorghum inbred lines.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches have found that high salt levels increase membrane lipids' unsaturated fatty acid contents in halophytes but not in A. thaliana (Table 4).As known o all, among halophytes, 18:3 is the predominant unsaturated fatty acid during NaCl stress. The x-3 desaturases transgenic tobacco improved resistance ability to salt and drought stress (Zhang et al, 2005), which implies the salt and drought tolerance of plant depends on the levels of unsaturated fatty acids (Berberich et al, 1998;Mikami & Murata, 2003). Synechocystis mutants, which lacked the activity of x-6 and x-3 desaturase, reduced the resistant ability to salt stress (Allakhverdiev et al, 2001).…”
Section: Discussionmentioning
confidence: 99%